P‐160: Improving MicroLED efficiency by p‐contract optimization - Qian, Yizhou; Hsiang, En-Lin; Huang, Yu-Hsin; Lin, Kuan-Heng; Wu, Shin-Tson (SID International Symposium Digest of technical papers, 2024)
Blue InGaN/GaN CPC microLED with metallic sidewall can achieve a higher efficiency based on the dipole cloud model in FDTD and electrical model in TCAD. By merely optimizing the p‐GaN contact size, the EQE is improved by 8.7%. Such method helps to achieve high brightness with a lower power consumption.